Scalp Advancement and the Pretrichial Brow Lift - Spiegel, Jeffrey H. (Facial Plastic Surgery, 2018)
This article will review considerations for scalp advancement, or forehead shortening, when done in combination with a brow lift. The author's technique for anterior hairline reshaping is presented with particular focus on simultaneous reduction of temporal recession.
Keywords: brow lift; scalp advancement; forehead; pretrichial incision